Definition and management of colorectal polyposis not associated with APC/MUTYH germline pathogenic variants: AIFEG consensus statement. Issue 4 (April 2021) - Urso, Emanuele Damiano Luca; Ponz de Leon, Maurizio; Vitellaro, Marco; Piozzi, Guglielmo Niccolò; Bao, Quoc Riccardo; Martayan, Aline; Remo, Andrea; Stigliano, Vittoria; Oliani, Cristina; Lucci Cordisco, Emanuela; Pucciarelli, Salvatore; Ranzani, Guglielmina Nadia; et al.
Abstract: An expert consensus panel convened by the Italian Association for Inherited and Familial Gastrointestinal Tumors ( Associazione Italiana per lo Studio della Familiarità ed Ereditarietà dei Tumori Gastrointestinali, AIFEG) reviewed the literature and agreed on a number of position statements regarding the definition and management of polyposis coli without an identified pathogenic mutation on the APC or MUTYH genes, defined in the document as NAMP (non- APC/MUTYH polyposis).